In the Name of Pauk-Phaw : Myanmar's China Policy Since 1948 - Aung Myoe, Maung (Book collections on Project MUSE., 2011)
Since its independence in January 1948, Myanmar has tried to find a way to deal with (at one time) ideologically hostile and traditionally chauvinistic China which has pursued a foreign policy aimed at restoring its perceived influence in Myanmar. To counter China's attempts to influence Myanmar's foreign policy options has always been a challenge for the Myanmar government. Since the 1950s, successive Myanmar governments have realized that Myanmar's bilateral relations with the People's Republic of China should best be conducted in the context of promoting the Five Principles of Peaceful Coex.